PERAN MEDIASI KEPUASAN KERJA PADA PENGARUH RETENSI KARYAWAN DAN LOYALITAS KERJA TERHADAP KINERJA KARYAWAN PADA RUMAH SAKIT UMUM MITRA KELUARGA HUSADA - Mahardika, Dwi Septian; Suddin, Alwi; Wardiningsih, Suprihatmi Sri (Universitas Slamet Riyadi, 2019)
The main element in determining the success or failure of an organization in carrying out various activities to achieve the objectives of various organizational goals is human resources. The success of an activity in an organization is determined by how humans manage it. Basically the goal of each organization is to achieve success in improving employee performance. The population of employees of Mitra Keluarga Husada General Hospital in 2019 was 94 people. Samples taken with census technical as many as 94 people. Conclusions of the research results: (1) The hypothesis states: